A systematic review of cost-effective methods of international humanitarian response - Erblin Shehu; Sheila Spahiu (Social Development and Security, 2021)
Humanitarian relief organizations face many challenges due to the increasing number of both natural and man-made disasters such as drought, famine, war, and conflict. According to the United Nations, these challenges will continue to increase because of the risen vulnerability of humanitarian supply chains, especially regarding cost, accuracy, and duration. In this systematic review, we explore methods of lowering the cost of humanitarian responses, more specifically in regard to the education and training of aid workers.